A conceptual framework: the influence of school culture types and personality traits on psychological empowerment amongst secondary school teachers in Malaysia / Leele Susana Jamian, Badjie Xbietaquauallah Ibadallah and Chan Yuen Fook. - Jamian, Leele Susana; Ibadallah, Badjie Xbietaquauallah; Chan, Yuen Fook (2019)
Educational reformers have considered teacher empowerment as one of the panaceas for school success. The concept of teacher empowerment has emerged as an important approach in promoting positive work behaviors with many researchers observing the link between the levels of teachers’ psychological empowerment and the extent to which they feel motivated, committed and satisfied with their job. Drawing from an ongoing doctoral research which looked at the relationships of school culture types and personality traits towards psychological empowerment amongst secondary school teachers in Malaysia, this article discusses the formulation of a conceptual framework. Although there have been numerous empirical researches on the structural and psychological constructs of teacher empowerment, previous studies mainly looked at these constructs in isolation. This current paper discusses the concept of empowerment and intends to model teacher empowerment as a holistic framework from multiple perspectives. The framework puts forward in this paper is based on both the literature and a study investigating the relationships of school culture types and personality traits towards psychological empowerment amongst teachers in the context of Malaysian secondary school. In addition, this paper also attempts to discuss the possible research issues that could justify the development of the conceptual framework of the topic.